Avaliação da atividade inibitória In vitro de bacteriocinas extraídas de Lactobacillus spp. isolados de aves (Gallus gallus, Linnaeus, 1758) - Lima, Edna Tereza de [UNESP] (2003)
Native intestinal lactic acid bacteria from poultry and mammals provide an adverse environment to development of pathogenic microorganisms. Recently, beyond its use as probiotics, the application in food conservation has been researched. Species like Lactobacillus, Lactococcus, Streptococcus, Pediococcus e Leuconostocs are used in fermented food, presenting antagonistic properties to same species and/or pathogenic bacterias. Lactobacillus spp. species used in probiotics and competitive exclusion products have benefic effects due direct action on particular groups of pathogenic microorganisms. Just by these advantages, lactic acid bacteria have been exhaustively studied allowing the detection of antibiose promoters substances as organic acids, bacteriophags, hydrogen peroxide, and bacteriocins. In the present study, 474 lactic acid bacteria from Lactobacillus species were isolated from the crop and ceca of chicken. Two hundred sixty five samples presented inhibitory activity against indicator microorganisms (Gram-positive and Gram-negative bacterias) using the spot-on-the-lawn assay. Fifty three samples identified as Lactobacillus reuteri, L. salivary and L. spp. confirmed inhibition of Enterococcus faecalis, E. faecium, Staphylococcus aureus, Listeria monocytogenes and Salmonella spp. but not on Lactobacillus casei, L. delbrureckii, L. fermentum and L. helveticus by bacteriocins action by antagonistic the simultaneons methods of well diffusion assay on anaerobiosis. The antagonism was detected by inhibition zones to various indicators microorganisms.